Creación de una base de datos homogeneizada de temperaturas para los Pirineos (1950-2010) - Cuadrat, José María; Serrano, Roberto; Saz, Miguel Ángel; Tejedor, Ernesto; Prohom, Marc; Cunillera, Jordi; Esteban, Pere; Soubeyroux, Jean Michel; Deaux, Nathalie (Geographicalia, 2014)
In this work we focused on create a climate database of 66 monthly temperature series in the period 1950-2010. Each series has been quality controlled and homogenized by HOMER script, which incorporates the latest methods and techniques on data management, including outlierremoving, pairwise detection, and breakpoint selection (enhanced by metadata). To evaluate the quality of initial series through the homogenization process is used the MDA (Minimum Detectable Amplitude) value. The final series provide homogenized data to analyze the evolution of the climate and climatic behaviour in the Pyrenees.